How Space Shapes the Everyday School Experience of Students and Professors at Križanke in Ljubljana - Babuder, Anuša (Lidé města, 2022)
This article centres on place attachment and feelings of belonging of students and professors of the Secondary School for Design and Photography, Ljubljana (SŠOF). The school’s educational practice is split between two locations: Križanke, a medieval complex in the city centre; and Roška, a renovated military barrack on Ljubljana downtown’s periphery, which SŠOF shares with another school. Students and professors in my research described Križanke as a “creative”, “free”, and “democratic” space where they felt like they belong, especially in contrast to the second location. My objective here is to understand how much of a role the actual place has in shaping the relationships between school environments and their users (students, professors). In the article, I present the historical context of Križanke and SŠOF’s current spatial crisis (threats of eviction from Križanke), followed by a “walk through Križanke” to examine students’ sensory perceptions of the building. This text analyses spatial elements like unique classroom set-ups, narrow corridors, and the labyrinthine construction of Križanke. These elements produce more informal and dynamic interactions between students and professors at SŠOF, which consequently enhance the students’ feelings of belonging, acceptance, and creativity. Finally, I conclude by examining how a complex interrelatedness between a sense of place, narration of place, and attachment to place in a school context impact the everyday learning experience at SŠOF and Križanke.